Globalization, Technological Developments, and the Work of Fiscal Termites - Tanzi, Vito (IMF Working Papers; Working Paper, 2000)
Deepening globalization and associated or parallel technological and institutional developments are creating conditions which may reduce the industrial countries' ability to sustain high levels of taxation. The paper identifies and discusses eight trends which may generate revenue falls. It also discusses some measures that might neutralize or reduce the impact of these trends.